The effect of metal surface nanomorphology on the output performance of a TENG - Wang, Yiru; Zhao, Xin; Liu, Yang; Zhou, Wenjun (Beilstein Journal of Nanotechnology, 2022)
In this work, the effect of charge density and nanomorphology of a metal tip on the output performance of a triboelectric nanogenerator (TENG) is studied. The basic working principle of the TENG is charge transfer after separation of a metal and a polymer. There are different charge densities on different kinds of metal surface nanomorphology, which significantly influences the output performance of the TENG. Copper samples with different nanomorphology were obtained by controlling pH value, current density, electrolyte concentration, and temperature during the electrodeposition of copper. The samples were characterized using XRD and SEM. The output performance of the TENG is closely related to the size, charge density distribution, and shape of the metal nanoparticles.
Keywords: charge density; green energy; metal nanomorphology; triboelectric nanogenerator (TENG)